Development of Interactive Multimedia on Learning Descriptive Text for French Learners in North Sumatra - Nurilam Harianja; Tengku Ratna Soraya; Hesti Fibriasari (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
Pandemic where the learning process cannot be done directly or face to face, especially in foreign language learning, especially French in class X in first semestre students who should receive the most basic French language learning. An interactive multimedia for French Learners in North Sumatra using Adobe flash professional CS6 software which aims to improve student motivation and learning outcomes in writing descriptive text material contained in the learning objectives decrire une personne et une chose. Interactive multimedia that is developed and implemented in learning is very important because it has been proven to be feasible and effective. The object of this research is the students of class X at SMA 21 Medan. The purpoese of the research is to develop interactive multimedia on descriptive text material for French learners in Notrh Sumatra and knowing the effectiveness of interactive multimedia products based on Adobe Flash Professional CS 6 to improve the ability to write descriptive text of students of SMA Negeri 21 Medan. This research was conducted using the R&D development research method by adapting the DDD-E development model, as for the interactive multimedia development steps for learning descriptive text writing skills for students of class XI SMA as follows: (1) Decide, (2) Design (product design) , (3) Development (product development), (4)) Evaluation (product test). To obtain data validity, validation of media experts and material experts. To obtain data validity, validation of media experts and material experts is required with the following results: (1) material validation shows the eligibility percentage is 88.5% in the very good category (2) media validation shows the Feasibility percentage is 87.3% with the very good category. The results of individual trials were declared "very good" with an average percentage of 82.7%. The results of small group trials were stated to be "very good" with an average percentage of 86.3% and the results of limited field trials were declared "very good" with an average percentage of 88.5%. Then, the effectiveness of interactive multimedia products is seen from the increase in student learning outcomes in descriptive text material before and after using interactive multimedia. There is a difference in value 22.30. This Interactive multimedia that is feasible and effective is used as a medium for teaching French in high school, especially class x semester 1, which must acquire basic French knowledge with a precise and interesting process during the Covid 19 pandemic.